The ‘Intense Ideological Activity’ of the 1919-20 Turin Factory Council Movement - Piu, Piermarco (International Gramsci Journal, 2023)
The article focuses of the activity of Gramsci, the Ordine Nuovo group and the communist vanguard in the Turin Factory Council movement throughout the ‘Red Biennium’ (1919-1920) and during the occupation of the Italian factories (September 1920). This movement questioned the owners’ power in the factory, with the occupation in Turin characterized by the workers collectively managing the plants without the owners. From this perspective, the Turin Factory Council movement and the local occupation represented one of the most advanced political and organizational developments of the Italian working class in the twentieth century. By applying ‘the molecular’ in directions that Gramsci would have found interesting, this article addresses how ideas and images of the Factory Councils circulated ‘mole-cularly’ within the Turin working class movement. This helps understand how the circulation affected the ‘spontaneous’ establishment of a ‘productive network’ of Councils during the Turin occupation. The ‘molecular’ focus shows that the Turin movement raised - without solving – one question of democratic relevance: how to overcome the division between leaders and led. By discussing this issue from a historiographical perspective, this article intervenes in the debates about September 1920 and the Red Biennium, asking to what extent the ideological work of Gramsci and the Ordine Nuovo group throughout 1919-1920 directed the spontaneous practices of the Turin workers during the occupation. Moreover, it sheds light on the emancipatory politics of 1919-1920, questioning whether the leaders-led distance was overcome in the production and circulation of conciliar ideas and images. Secondly, from a theoretical perspective, the molecular approach and the question of democracy are used to explore the theoretical and political lexicon of the Prison Note-books – particularly hegemony and the direction of spontaneity. The article discusses the molecular functioning of these two issues, arguing that an emancipatory hegemony cannot rely solely on the direction of spontaneity to address the leaders-led division. As such, the intellectuals and subalterns’ coproduction of theoretical perspectives emerges as one of the political and practical challenges for an emancipatory hegemony, particularly during the Red Biennium.